2011
DOI: 10.1016/j.amjmed.2011.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia-associated Mortality Is Not Drug-associated but Linked to Comorbidities

Abstract: Objective Although tight glucose control is widely used in hospitalized patients, there is concern that medication-induced hypoglycemia may worsen patient outcomes. We sought to determine if the mortality risk associated with hypoglycemia in hospitalized non-critically ill patients is linked to glucose-lowering medications (drug-associated hypoglycemia) or if it is merely an association mediated by comorbidities (spontaneous hypoglycemia). Methods Retrospective cohort of patients admitted to the general ward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
130
3
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(148 citation statements)
references
References 31 publications
(40 reference statements)
5
130
3
6
Order By: Relevance
“…[22] However, other studies suggest that the increased mortality rate associated with hypoglycemia is only with spontaneous hypoglycemia rather than drug-associated hypoglycemia. [23] The causes of hypoglycemia in hospitalized T2DM patients include continued hypoglycemic therapy, such as sulfonylureas, when caloric intake is stopped or reduced, use of standard sliding-scale insulin inadequately, [24] errors in insulin dosing, and implementation of intensive insulin therapy in critically ill patients. [25] Prolonged QT interval, ischemic electrocardiogram changes, arrhythmias, and sudden death are also associated with hypoglycemia.…”
Section: Treatment Of Hypoglycemiamentioning
confidence: 99%
“…[22] However, other studies suggest that the increased mortality rate associated with hypoglycemia is only with spontaneous hypoglycemia rather than drug-associated hypoglycemia. [23] The causes of hypoglycemia in hospitalized T2DM patients include continued hypoglycemic therapy, such as sulfonylureas, when caloric intake is stopped or reduced, use of standard sliding-scale insulin inadequately, [24] errors in insulin dosing, and implementation of intensive insulin therapy in critically ill patients. [25] Prolonged QT interval, ischemic electrocardiogram changes, arrhythmias, and sudden death are also associated with hypoglycemia.…”
Section: Treatment Of Hypoglycemiamentioning
confidence: 99%
“…Hypoglycemia has been associated with mortality in multiple intensive care unit studies, but this association is not as clear on the medical wards. [1][2][3][4] Hypoglycemia in the outpatient setting is a recognized risk factor for mortality and morbidity including cardiovascular, cerebrovascular, and patient fall events. 5,6 The prevalence of hypoglycemia (<70 mg/dl) was reported to be 5.7% of all point-of-care blood glucose (BG) tests in a 2009 survey of 575 hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study of a large cohort of patients with or without diabetes, admitted to Departments of Internal Medicine, showed that mortality was higher among patients who had spontaneous hypoglycemias. 17 After adjustment for comorbidities, hypoglycemia was no longer an independent risk factor for mortality, thereby reinforcing the concept that hypoglycemia acts as a marker of severe underlying disease, rather than as a direct cause of death. Similar results were found in patients with AMI, about 50% of them diabetics.…”
Section: Consequences Of Hypoglycemiamentioning
confidence: 88%
“…Risk factors for spontaneous hypoglycemia are septic shock, comorbidities (as defined by the Charlson comorbidity index), drug interactions in polypharmacy, renal failure, liver or adrenal disease, severe heart failure and neoplasms. 17,18 We have always to remember that during hospitalization, patients undergo changes of their insulin sensitivity and counter-regulatory hormone, secondary to the disease, procedures and treatment carried out. 19,20 Older patients also have often organ dysfunction age related, which alters insulin sensitivity and drug metabolism, resulting in the enhancement of hypoglycemic events.…”
Section: Risk Factors Of Hypoglycemiamentioning
confidence: 99%
See 1 more Smart Citation